Flaubert’s Dig: From Fragments to Modernity's Emerging Form - Suzanne Braswell (Flaubert: Revue Critique et Génétique)
The curiously fragmented form of Gustave Flaubert's La Tentation de saint Antoine and his final and incomplete novel Bouvard et Pécuchet seems anomalous in comparison to his more well-known works. However, these works occupied Flaubert's consciousness over decades of his lifetime. Indeed, he returned three times to La Tentation, a text he characterized as “plus étrange que beau”, and devoted years of research to Bouvard et Pécuchet, suggesting a project of equally enduring interest for the writer. If these two novels seem to stand apart from the rest of his opus, they were in fact the fruit of two abiding lines of interest for the author: theatrical forms and the poetic potential of narrative form, explored through tableaux and fragmentation. This analysis considers the poetics of discontinuity and its relationship both to popular theatrical forms of mid-nineteenth-century France and to emerging characteristics of modernity, notably fragmented consciousness.